Perfil proteômico durante o desenvolvimento do zebrasfish sob efeitos de espécies químicas de manganês e as implicações na neurotoxicologia deste material - Pinto, Pedro Jose Amorim [UNIFESP] (2016)
Manganese (Mn) is an essential element for all forms of life, but may also be neurotoxic in acute or chronic exposure coming be associated with various diseases such as Alzheimer's or Parkinsonism. However, Mn neurotoxicity mechanisms are still not fully understood. Accordingly, the search for biomarkers of Mninduced neurotoxicity is one of the great challenges. Precisely, the toxicoproteomics has been driven to the development of new diagnostic biomarkers and the identification of new therapies in cases of intoxication and / or diseases. Through proteomic analysis can be identified proteins with intensity variation during the development of zebrafish embryos. This study aimed to compare the protein maps of zebrafish embryos in the period 48 ? 120 hours post-fertilization (hpf), exposed in citrate solutions 6 mM, Mn(II)Cit 1,5 mM and MnCl2 1,5 mM. To obtaining the protein profiles was used the method of two-dimensional electrophoresis coupled to mass spectrometry. The gels were analyzed with PDQuest software and finally identification by mass spectrometry (Nano HPLC MS-MS), accompanied by a query in the protein database (Mascot). Both treatments MnCl2 and Mn(II)Cit induced changes in the proteome of zebrafish embryos; and 15 spots showed significant differences in expression (p <0.05), where 13 proteins were identified, which are involved in the structural composition of the cytoskeleton, constituents of the extracellular matrix, myelin sheath and ribosomes. These results suggest that damage induced by manganese species should be associated with biogenesis of ribosomes as well as the organization and polymerization of the cytoskeleton; impairment of the stress response pathways, redox signaling mechanism, cellular organization, muscle contraction, cellular signaling and energy metabolism. Finally, both manganese chemical species induced changes in cell growth and differentiation, mitosis, and apoptosis.